Global Gene Expression Profiling Reveals Isorhamnetin Induces Hepatic-Lineage Specific Differentiation in Human Amniotic Epithelial Cells - Uchida, Yoshiaki; Ferdousi, Farhana; Zheng, Yun-Wen; Oda, Tatsuya; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2020)
Human amnion epithelial cells (hAECs), derived from discarded term placenta, is anticipated as a new stem cell resource because of their advantages over embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), such as no risk of tumorigenicity and minimal ethical issue. hAECs have been reported to differentiate into hepatocyte-like cells (HLCs) with variable functionalities suitable for cell-based therapy of end-stage liver diseases, drug screening, and drug toxicity tests. On the other hand, a new research stream has been evolving to use natural compounds as stimulants of stem cell differentiation because of their high availability and minimum side effects. Isorhamnetin is a naturally occurring flavonoid commonly found in fruits and vegetables and has been reported to improve hepatic fibrosis and steatosis. In this present study, we have screened the differentiation potential of isorhamnetin in hAECs. The cells were grown on 3D cell culture and were treated with 20 uM of synthesized isorhamnetin for ten days without adding any additional growth factors. DNA microarray global gene expression analysis was conducted for differentially expressed genes between isorhamnetin-treated and untreated control cells, gene expression validation was carried out using RT-qPCR method, and finally, several hepatic functions were assessed. Microarray analysis showed that isorhamnetin could activate essential biological processes, molecular functions, and signaling pathways for hepatic differentiation. Hepatic progenitor markers, EPCAM and DLK1, were upregulated in the isorhamnetin-treated hAECs. AFP was downregulated, while ALB was upregulated on Day 10. Furthermore, isorhamnetin-treated cells could show inducible CYP enzyme mRNA levels, ICG uptake and release, glycogen storage activity, and urea secretion. Additionally, isorhamnetin-treated cells did not show any trace of transdifferentiation evident by significant downregulation of several colon- and cholangiocyte-specific markers. However, longer treatment with isorhamnetin did not promote hepatic maturation. Altogether, our findings indicate that isorhamnetin has a promising effect on hAEC differentiation into hepatocyte-like cells.